Whistles, Words, and Willpower: How Coach Etiquette Relates to Intrinsic and Extrinsic Sport Motivation among Collegiate Softball And Baseball Athletes - Olivia Dimatulac; Ronald Librando; Jojielyn Lim; Jasper Obanon; Lloyd Neo Oalog; Rhea Mae Oblima (INSPIREE: Indonesian Sport Innovation Review, 2026)
The  purpose  of  the study. This study examined whether perceived coach etiquette predicts intrinsic and extrinsic sport motivation among collegiate softball and baseball athletes in a selected Philippine university. Materials and methods. A quantitative, descriptive, cross-sectional (non-experimental) design was employed. Forty-five varsity athletes (softball n=23; baseball n=22; female n=23; male n=22) completed a survey packet consisting of (a) a modified Perceived Coach Attitudes and Behaviors Scale (PCABS; 28 items; 4-point response format) to capture coach etiquette-related behaviors and (b) the Sport Motivation Scale-II construct coverage (23 items; 4-point response format) to capture athletes’ motivational regulations. Descriptive statistics summarized perceived etiquette and motivation. Linear regression tested the hypothesized predictive effect of coach etiquette on intrinsic and extrinsic motivation (α=0.05). Results. Athletes perceived coaches’ etiquette as a moderate degree of respect (overall M=3.03). Athletes reported strong sport motivation (overall M=3.69). Regression analyses indicated that coach etiquette did not significantly predict intrinsic motivation (t=0.846, p=0.4023) or extrinsic motivation (t=1.33, p=0.2636). Conclusions. Coach etiquette was positively perceived but did not significantly explain intrinsic or extrinsic motivation in this cohort. Future work should include autonomy-supportive coaching, motivational climate, and psychological need satisfaction as potential mediators/moderators.